Study into the influence of concentration of ions of chlorine and temperature of circulating water on the corrosion stability of carbon steel and cast iron - Pancheva, Hanna; Reznichenko, Ganna; Miroshnichenko, Nataliya; Sincheskul, Alexander; Pilipenko, Alexei; Loboichenko, Valentyna (Технологический центр, 2017)
The impact of the chloride ions concentration and the temperature of the circulating water on the process of corrosion destruction of carbon steel and cast iron has been investigated. It has been shown that an increase in the concentration of chloride ions causes a shift in the values of the stationary potentials of steel and cast iron to the region of negative values and reduces the passive state of these alloys. This leads to an increase in the corrosion rate of St.3 steel and CI 18-36 cast iron. The results of electrochemical studies have shown that the more reliable protective films are formed on steel than on cast iron. The limiting concentration of NaCl, at which reliable operation of equipment made from these alloys is possible, depends on the pH of the solution. At pH=7, it is about 1.2 g l⁻¹, which is about an order of magnitude less than at pH=12. When the circulating water temperature rises, the corrosion rate of steel and cast iron increases. The stationary potentials of steel and cast iron are shifted to the negative range, and the polarization of the anode process decreases. Corrosion process is limited by the rate of oxygen supply to the cathode areas.

Досліджений вплив концентрації іонів хлору і температури оборотної води на процес корозійного руйнування вуглецевої сталі і сірого чавуну. Встановлено, що збільшення концентрації хлорид-іонів обумовлює зміщення величин стаціонарних потенціалів сталі і чавуну в область негативних значень і зменшує область пасивного стану зазначених сплавів. В результаті проведених досліджень встановлено, що обладнання, виготовлене з сталі Ст. 3 і чавуну СЧ 18-36, можна використовувати в оборотній воді з рН=12, що містить до 10 г∙л⁻¹∙NaCl при температурі не більше 40 °C.
Вплив концентрації іонів хлору і температури оборотної води на процес корозійного руйнування вуглецевої сталі і сірого чавуну
Keywords: circulating water; corrosion process; chloride ions; passivity; polarization dependence; pitting; oxide-hydroxide films; оборотна вода; корозійний процес; хлорид-іони; поляризаційна залежність; пітінг; оксидно-гідроксидні плівки